Retracted: Research on image sharpening algorithm in weak illumination environment. Issue 15 (24th July 2020) - Niu, Jinxing; Jiang, Yajie; Fu, Yayun
Abstract : Owing to low light intensity, the image detector is underexposure, the colour and contrast of scene images will be changed, so it is of great significance to study the image sharpening in a weak illumination environment. In this study, the causes of image blurring are firstly analysed by histogram equalisation (HE) and retinex theory. A method combined HE and multi‐scale retinex theory with colour recovery is proposed. The experimental simulation results show that the image processing effect of this algorithm is the most obvious, the local details and dark areas are clearly visible, the colour is rich, and the visual effect is the best, which has a certain practical application value.